A general model for carbon isotopes in red-lineage phytoplankton: Interplay between unidirectional processes and fractionation by RubisCO. (15th November 2019) - Wilkes, Elise B.; Pearson, Ann
Abstract: The carbon isotopic composition of organic matter preserved in marine sediments provides a window into the global carbon cycle through geologic time, including variations in atmospheric CO2 levels. Traditional models for interpreting isotope records of marine phytoplankton assume that these archives primarily reflect kinetic isotope discrimination by the carbon-fixing enzyme RubisCO. However, some in vivo and in vitro measurements appear to contradict this assumption, indicating that significant questions remain about the mechanistic underpinning of algal isotopic signatures, including the role of carbon concentrating mechanisms (CCMs). Here, we present a general model to explain photosynthetic carbon isotope fractionation ( ε P ) in marine red-lineage phytoplankton groups; the model reproduces existing chemostat and batch culture datasets with a normalized root mean squared error (nRMSE) of 6.8%. Our framework proposes that a nutrient- and light-dependent step upstream of RubisCO is a kinetic barrier to carbon acquisition and therefore represents a significant source of isotopic fractionation. We suggest this step represents a carbon concentrating strategy that becomes favorable to cells under conditions of excess photon flux. The primary implications are that RubisCO is predicted to exert minimal isotopic control in photon-rich, nutrient-limited regimes but becomes influential as growth becomes light-limited. This framework enables both environment-specific and taxon-specific isotopic predictions. By refining the mechanistic understanding of marine photosynthetic carbon isotope fractionation, we may begin to reconcile existing datasets and reexamine Phanerozoic isotope records—including the resulting CO2 reconstructions—by emphasizing the influence of different types of resource limitation on photosynthetic carbon acquisition.